Constructing and Evaluating the Features of Novelty Yarn Made from Denim Cut Waste - Rahman, Mohammad Mizanur; Reza, Md. Alimur; Rabea, Nishat; Dola, Dilshat Rubia; Farin, Faijun (European Journal of Applied Sciences, 2023)
By turning the apparel industry denim cut waste into mélange yarn, the study aims to help the sector get toward zero waste. It is crucial to create already-available manufacturing techniques that are more environmentally friendly. Being conscious of environmental issues, it is a rapidly expanding section of the fashion industry. The major issue facing the enormous denim business is caused by vast amounts of secondhand waste, unsalable stock, and denim waste that needs to be treated from scratch. In order to prepare cotton for the production of recycled cotton yarns, recycled cotton fiber was first extracted from denim cut waste using mechanical procedures (sorting & opening - extraction of fiber, sliver development, drawing, roving, spinning). The fiber was dyed without going through the dyeing process, and recycled cotton was used to create the yarn. The yarn underwent tests to determine its strength (153 lb./lea, TPI 17, count 8 Ne), applicability as a raw material for clothing, and more. According to other findings, it is a high-quality complete yarn because mélange yarn, for various ratios, Because there is no blending of two different fibers, 100% cotton yarn has produced the best results. This method of recovering denim cut waste in the textile manufacturing sector today is efficient and sustainable.